Mitigating effects of acetylcholine supply on soybean seed germination under osmotic stress - Braga, Inaê [UNESP]; Pissolato, Maria Dolores; Souza, Gustavo Maia (Springer Nature, 2017)
Acetylcholine (Ach) is a common neurotransmitter in animals, also synthesized in plants, which can have an influence on plant response to stress, also acting as a signaling molecule between root and shoot. The objective of this study was to analyze the possible mitigating effects of exogenous application of Ach on soybean germination under different levels of osmotic potential. The experiments were conducted with soybean [Glycine max (L.) Merrill] genotype Intacta. The seeds were first treated with Ach solutions with the following concentrations: 0.0 (control); 0.5; 1. 0 and 2.0 mM. Then, the seeds were subjected to two water potentials, −0.5 and −1.0 MPa, reached by using mannitol solutions, for the induction of osmotic stress, and a control condition with distilled water. Thus, 12 treatments were established in a double factorial 4 × 3, with 4 levels of Ach and 3 osmotic potential treatments (0.0, −0.5 and −1.0 MPa) with four replicates per treatment. The results showed that the concentration of 1.0 mM Ach, without osmotic stress, presented higher values for total dry mass of the seedlings compared to the control treatment (without Ach supply). In the treatments conducted to test the effectiveness of Ach on the mitigation of severe osmotic stress effects (−1.0 MPa), results showed that the concentration of 0.5 mM Ach showed positive results for the following parameters; dry weight of shoot, root dry weight, total dry mass, which were significantly higher than treatment under 1.0 MPa.
Keywords: Abiotic stress; Glycine max; Neurotransmitter; Seedling growth